Understanding the impact of cascade effects of natural disasters on disaster relief operations. (June 2015) - Berariu, Romana; Fikar, Christian; Gronalt, Manfred; Hirsch, Patrick
Abstract: This paper analyzes cascade effects of natural disasters and investigates their impact on relief operations with respect to critical infrastructure, in particular, the transport infrastructure, electricity and human health. Causal-Loop-Diagrams (CLDs) are generated in order to provide useful information for decision makers. CLDs clearly visualize cascade effects which enable one to identify non-linear critical feedback processes and to analyze the behavior of the considered system. In order to investigate if the identified behavior occurred in real-world cases, we apply the CLDs to concrete natural disaster events, the European flood of 2002 and the European heat wave of 2003. Independent of the type of disaster, it can be concluded that cascade effects negatively affect critical infrastructure. The impacts on disaster relief operations can be proven for the case of the flood of 2002. In case of the heat wave of 2003 some of the assumed interdependencies did not appear in that analysis. The analysis shows that cascade effects and interdependencies between the different sectors of critical infrastructure can be visualized by the presented CLDs and are of high importance in order to understand their impact on disaster relief operations.